Pharmacokinetics/Pharmacodynamics of β-Lactams and Therapeutic Drug Monitoring: From Theory to Practical Issues in the Intensive Care Unit - Williams, Paul; Cotta, Menino Osbert; Roberts, Jason A. (Seminars in Respiratory and Critical Care Medicine, 2019)
Despite therapeutic advances over recent decades, the mortality rate for sepsis and septic shock is still approximately 25% worldwide. Early administration of appropriate intravenous antibiotics in the right dose is one of the cornerstones of treatment of sepsis. β-Lactam antibiotics are the most commonly prescribed in critically ill patients, and dosages that do not achieve specific pharmacokinetic/pharmacodynamic targets may increase the likelihood of treatment failure and even emergence of antibiotic resistance. Fluctuations in physiological parameters are often observed in critically ill patients, leading to altered pharmacokinetics and increased risk of suboptimal exposures, especially if standard dosing according to the product information is prescribed. Contemporary evidence illustrates that therapeutic β-lactam concentrations are inconsistently achieved at steady state. This review will investigate alternative β-lactam dose optimization strategies including prolonged infusions, guideline-based dosing, therapeutic drug monitoring (TDM), and the use of dose optimization software, all of which aim to increase the likelihood of achieving therapeutic drug concentrations and improve clinical outcomes as compared with the standard dosing approach. These dose optimization strategies have been the subject of a growing body of evidence; however, further investigation into the outcome benefits and validity of both non-TDM and TDM dosing strategies is required. For the clinician, it is important to select a feasible dosing strategy tailored for the individual patient, which will maximize the likelihood of achieving therapeutic concentrations at steady state and maintain these exposures throughout the course of therapy.
Keywords: β-lactam; pharmacokinetics; pharmacodynamics; critically ill; guideline; therapeutic drug monitoring; dose optimization software